2024
DOI: 10.1128/mmbr.00042-23
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the cellular biology, biochemistry, and molecular biology of acidocalcisomes

Roberto Docampo

Abstract: SUMMARY Acidocalcisomes are organelles conserved during evolution and closely related to the so-called volutin granules of bacteria and archaea, to the acidocalcisome-like vacuoles of yeasts, and to the lysosome-related organelles of animal species. All these organelles have in common their acidity and high content of polyphosphate and calcium. They are characterized by a variety of functions from storage of phosphorus and calcium to roles in Ca 2+ signaling, osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 231 publications
0
7
0
Order By: Relevance
“…Acidocalcisomes provide another paramount function, since they are also capable of accumulating large quantities of phosphorus, present as phosphates, pyrophosphates, and polyphosphates, together with an enzyme with pyrophosphatase activity. This fact is relevant for parasite bioenergetics since it has been shown that pyrophosphate constitutes an alternative energy source to ATP, and is frequently used in many transporting functions in trypanosomatids [23]. A proton-pumping pyrophosphatase similar to the present one in acidocalcisomes has also been localized and characterized at the plasma membrane and at the Golgi apparatus of T. cruzi, thus revealing its ubiquity in these parasites [26].…”
Section: Intracellular Ca 2+ Regulation In Trypanosomatids and Compar...mentioning
confidence: 88%
See 4 more Smart Citations
“…Acidocalcisomes provide another paramount function, since they are also capable of accumulating large quantities of phosphorus, present as phosphates, pyrophosphates, and polyphosphates, together with an enzyme with pyrophosphatase activity. This fact is relevant for parasite bioenergetics since it has been shown that pyrophosphate constitutes an alternative energy source to ATP, and is frequently used in many transporting functions in trypanosomatids [23]. A proton-pumping pyrophosphatase similar to the present one in acidocalcisomes has also been localized and characterized at the plasma membrane and at the Golgi apparatus of T. cruzi, thus revealing its ubiquity in these parasites [26].…”
Section: Intracellular Ca 2+ Regulation In Trypanosomatids and Compar...mentioning
confidence: 88%
“…Also, they are acidic organelles, being acidified by a vacuolartype proton-translocating (V-H + -ATPase) pump. Acidocalcisomes are, in various ways, similar to the vacuole present in fungi and plant cells, but have no counterpart in mammal cells [22,23]. Acidocalcisomes undoubtedly deserve more investigation due to their function in intracellular Ca 2+ homeostasis, their direct relation with infectivity of the parasite, and their connection with pH regulation and with osmoregulation, among other important roles in these parasites [23].…”
Section: Intracellular Ca 2+ Regulation In Trypanosomatids and Compar...mentioning
confidence: 99%
See 3 more Smart Citations